Cross-Cultural Conflict Management: Communication Challenges and Mediation Strategies in Multinational Teams Systematic Literature Review - Septiyanti, Fauziyah Mubaarokah; Anshori, M Isa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Market changes due to globalization do not only require companies to make changes in terms of territory but also include company operations in order to be accepted globally. Cross-cultural conflict management is an important aspect that must be present in multinational companies because it can help companies in the management and resolution process that arises due to cultural diversity in the team. This study was conducted with the aim that company managers can face the challenges of globalization and adapt to a diverse international environment. The research method chosen was a systematic literature review with a time span of the last five years. The results of the study indicate that cultural diversity can cause challenges in the communication process. However, communication can also be used as a mediation strategy supported by cultural awareness, cross-cultural communication, training and effective leadership by company managers.